Fonseca S Funeral: Political Strategies in Chilean Communist Illegality, July 1949 [el Funeral de Fonseca: Estrategias Políticas en la Ilegalidad Comunista, Julio de 1949 - Rojas-Flores, J (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2020)
Ricardo Fonseca s funeral was not only the posthumous tribute to who had been General Secretary of the Chilean Communist Party. In the context of the political proscription that affected the communists, the organization of the funerals, in mid-1949, became an effective political tool that sought to influence that complex scenario, demonstrating the strength that could still be deployed and reinforcing its own party identity, affected by its virtual marginalization of political life. This was expressed in the thorough preparation of the funeral, the monumental character that adopted the ritual and the impact it had on other political actors. © 2020 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.